Pre-service Social Studies Teachers’ Perception of the Impact of Literacy on Teaching Quality - Nalle, Maha Dewi Sabrina (Jurnal Ilmiah Mandala Education (JIME), 2025)
Indonesians’ literacy skills are left behind compared to other Asians countries. Literacy skills are essentials for social studies subject; hence, the teachers are compelled to prepare and improve their teaching quality to lead students increase their literacy skills. This study aims to examine the perception of pre-service social studies teachers regarding literacy and its impact to their teaching quality. This study uses a qualitative study approach, the data were collected from semi-structured interview of 6 pre-service social studies teachers chosen with purposive sampling. The results shown that pre-service teachers social studies perceive literacy play important role in enhancing teaching quality. The suggestion is pre-service teachers are educated by integrating technology-based literacy methods to enhance their critical reading skills and ultimately improve their future teaching quality.